2021
DOI: 10.3390/molecules26165081
|View full text |Cite
|
Sign up to set email alerts
|

Olive Trees By-Products as Sources of Bioactive and Other Industrially Useful Compounds: A Systematic Review

Abstract: The need to produce an ever-increasing quantity of material products and food resulting from the planet globalization process has contributed to the spread of modern agriculture based on a linear production resulting in the generation of tons of waste. This huge amount of waste is generally accumulated in landfills, causing different environmental problems. Hence, researchers moved on to study the processes used to recover agro-industrial by-products within a circular and sustainable bio-economy concept. A sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 116 publications
(154 reference statements)
0
4
0
Order By: Relevance
“…ROS are also the major responsible for lipid-containing food degradation, which makes it necessary to add synthetic antioxidants to food. However, in the last years, several investigations demonstrated that synthetic antioxidants generally used by food industries, such as butylated hydroxytoluene (BHT), tert-butylhydeoquinone (TBHQ), and butylated hydroxyanisole (BHA), are not without side effects for human health [ 24 ]. For this reason, the research of a new safe antioxidant from natural origin is demanded.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are also the major responsible for lipid-containing food degradation, which makes it necessary to add synthetic antioxidants to food. However, in the last years, several investigations demonstrated that synthetic antioxidants generally used by food industries, such as butylated hydroxytoluene (BHT), tert-butylhydeoquinone (TBHQ), and butylated hydroxyanisole (BHA), are not without side effects for human health [ 24 ]. For this reason, the research of a new safe antioxidant from natural origin is demanded.…”
Section: Discussionmentioning
confidence: 99%
“…The peak numbers 6-8 present several similarities with oleuropein and oleuropein derivatives, such as dihydro-oleuropein and oleuropein aglycone. These compounds were detected in several olive fruit by-products [54][55][56], since they are a degrading form of olive fruits' secoiridoids, i.e., oleuropein and dimethyloleuropein, which occur during crushing/malaxation, thus forming several secoiridoid aglycone derivatives [25,57]. Moreover, fruit flavonoids such as luteolin-7-O-glucoside and rutin, as well as cinnamic acid esters such as verbascoside and comselogoside, have been reported in fruit derivatives (paste, pomace, and wastewater) [25], indicating their preferred transfer to waste without many alterations.…”
Section: Identification Of Phenolic Compoundsmentioning
confidence: 99%
“…Significant medical benefits are provided by the leaves, fruits, and oil. When infused or decocted, the leaves help regulate type II diabetes, decrease moderate hypertension, promote urine elimination, and protect against viral, bacterial, or fungal infections (Lo Giudice et al, 2021).…”
Section: Olive Tree Categories In Tunisiamentioning
confidence: 99%